Serum potassium is a predictor of incident diabetes in African Americans with normal aldosterone: the Jackson Heart Study. Issue 2 (14th December 2016) - Chatterjee, Ranee; Davenport, Clemontina A; Svetkey, Laura P; Batch, Bryan C; Lin, Pao-Hwa; Ramachandran, Vasan S; Fox, Ervin R; Harman, Jane; Yeh, Hsin-Chieh; Selvin, Elizabeth; Correa, Adolfo; Butler, Kenneth; et al.
ABSTRACT: Background: Low-normal potassium is a risk factor for diabetes and may account for some of the racial disparity in diabetes risk. Aldosterone affects serum potassium and is associated with insulin resistance. Objectives: We sought to confirm the association between potassium and incident diabetes in an African-American cohort, and to determine the effect of aldosterone on this association. Design: We studied participants from the Jackson Heart Study, an African-American adult cohort, who were without diabetes at baseline. With the use of logistic regression, we characterized the associations of serum, dietary, and urinary potassium with incident diabetes. In addition, we evaluated aldosterone as a potential effect modifier of these associations. Results: Of 2157 participants, 398 developed diabetes over 8 y. In a minimally adjusted model, serum potassium was a significant predictor of incident diabetes (OR: 0.83; 95% CI: 0.74, 0.92 per SD increment in serum potassium). In multivariable models, we found a significant interaction between serum potassium and aldosterone ( P = 0.046). In stratified multivariable models, in those with normal aldosterone (<9 ng/dL, n = 1163), participants in the highest 2 potassium quartiles had significantly lower odds of incident diabetes than did those in the lowest potassium quartile [OR (95% CI): 0.61 (0.39, 0.97) and 0.54 (0.33, 0.90), respectively]. Among those with high-normal aldosterone (≥9 ng/dL, n = 202), we found no significant association between serum potassium and incident diabetes. In these stratified models, serum aldosterone was not a significant predictor of incident diabetes. We found no statistically significant associations between dietary or urinary potassium and incident diabetes. Conclusions: In this African-American cohort, we found that aldosterone may modify the association between serum potassium and incident diabetes. In participants with normal aldosterone, high-normal serum potassium was associated with a lower risk of diabetes than was low-normal serum potassium. Additional studies are warranted to determine whether serum potassium is a modifiable risk factor that could be a target for diabetes prevention. This trial was registered at clinicaltrials.gov as NCT00415415.